Kaundinyapur plant economy in protohistoric and historic times - Vishnu-Mittre (Journal of Palaeosciences, 1966)
The paper describes carbonized food grains and their impressions from Kaundinyapur a site in Madhya Pradesh. The remains include cereals (rice and ? maize), legumes (peas) and the fruit remain (jujube) and a crushed fragment of a bamboo. The various strata from which the material has been recovered range in age from 500 B.C. to 1400 A.D. representing slightly earlier Mauryan to the Muslim Period.